Opción cero - Justiniano, José Guillermo (Drogas - el debate boliviano, 1994)
"Collection focuses on Bolivian government's plan (Opción Cero), to resettle coca leaf growers en masse from the Chapare region to another part of the country. Includes views of social scientists, US and Bolivian government policymakers, journalists, political activists, and other opinion makers"--Handbook of Latin American Studies, v. 57